AN ANALYSIS OF IMPLEMENTATION OF LEARNING SPEAKING ONLINE CLASS USING VIDEO FOR KIDS STUDENT AT BAHASAKU INGGRIS PARE KEDIRI - Fatqu Rofiqoh Dewi; Intan Zulina Risti (IAI Al-Qolam, 2022)
Speaking is one of the most important aspects in the language learning process to express ideas, feelings, experiences and knowledge, therefore students need the video method to facilitate learning activities. This study aims to explore student learning under the age of 12 to make it easier and feeling fun when learning. This research is a Qualitative research which consists of one class. Involved me as a researcher and English teacher from 10 students of the English For Kids level Bahasaku Inggris Course Pare Kediri. The steps of this research are reconnaissance, action planning, implementation and observation of the actions taken. The data of this research is qualitative. Qualitative data obtained by observation the teaching and learning process during the implementation of the action. Data were collected in the form of transcripts of the questionnaire. The research findings show that the implementation using video in speaking learning is effective in improving students' learning. Keywords: Speaking learners, Online Class, Video